2017
DOI: 10.1016/j.ijcard.2017.03.125
|View full text |Cite
|
Sign up to set email alerts
|

Early changes of left ventricular filling pattern after reperfused ST-elevation myocardial infarction and doxycycline therapy: Insights from the TIPTOP trial

Abstract: Aim: Metalloproteinases inhibition by doxycycline reduces cardiac protein degradation at extracellular and intracellular level in the experimental model ischemia/reperfusion injury. Since both extracellular cardiac matrix and titin filaments inside the cardiomyocyte are responsible for the myocardial stiffness, we hypothesized that doxycycline could favorably act on left ventricular (LV) filling pressures in patients after reperfused acute ST-elevation myocardial infarction (STEMI). Methods and results: Sevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
(62 reference statements)
0
6
0
1
Order By: Relevance
“…All animals were treated and cared for in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals (8th ed., Washington, DC: The National Academies Press, 2011), and all protocols were approved by the University of South Carolina's Institutional Animal Care and Use Committee. Serial experiments were carried out until 28 days post-MI because this time period encompasses a rapid change in LV geometry and function in both animals and patients (3,6,7,33). After the final set of LV function measurements, LV regions were subjected to mRNA analysis for myofibroblast phenotype expression (14,32,35,41).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All animals were treated and cared for in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals (8th ed., Washington, DC: The National Academies Press, 2011), and all protocols were approved by the University of South Carolina's Institutional Animal Care and Use Committee. Serial experiments were carried out until 28 days post-MI because this time period encompasses a rapid change in LV geometry and function in both animals and patients (3,6,7,33). After the final set of LV function measurements, LV regions were subjected to mRNA analysis for myofibroblast phenotype expression (14,32,35,41).…”
Section: Methodsmentioning
confidence: 99%
“…The reasons for the failure of this initial post-MI clinical trial were likely multifactorial and included problematic issues, from dosing and reaching therapeutic levels to that of small cohorts of patients enrolled from national and international sites with surprisingly modest degrees of LV remodeling post-MI. In a more recent study using doxycycline that putatively influenced MMP activity, LV functional outcomes were improved in patients with a significant MI (6,7). Moreover, this clinical trial identified shifts in plasma profiles of the endogenous tissue inhibitors of metalloproteinase (TIMPs), which were associated with indexes of LV remodeling post-MI (38).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Clinical studies pointed out a significant increase in plasma levels of MMPs in the early MI phase, which was also linked to adverse LV remodelling [ 157 , 158 ]. Though a few clinical studies have already targeted MMPs in MI patients, therapeutic outcomes were not completely clear due to issues related to limited sample size, a modest degree of LV remodelling, difficult targeted delivery and problematic dose up to significant therapeutic levels [ 159 ]. Indeed, targeting the MMP system to circumvent adverse LV remodelling post-MI holds therapeutic relevance.…”
Section: Functionalised Acellular Scaffoldsmentioning
confidence: 99%
“…Зниження фракції викиду лівого шлуночка може бути наслідком зниженої скорочувальної функції серця через обширне пошкодження міокарда або наслідком дилатації лівого шлуночка, викликаної поширенням зони інфаркту і розтягуванням рубцевої області міокарда. Функція лівого шлуночка є важливим предиктором результату ГІМ [5,6].…”
unclassified